THERAPEUTIC EFFECTS OF TRANSCUTANEOUS ELECTRICAL NERVE STIMULATION (TENS) AND THERAPEUTIC EXERCISES IN PATIENTS WITH CERVICAL SPONDYLOSIS. A PRELIMINARY STUDY - Galina Mratskova (Science & Research, 2020)

(untitled)
Aim: To evaluate the therapeutic effects of complex rehabilitation, including TENS - Transcutaneous electrical nerve stimulation and therapeutic exercises on pain and mobility in the cervical spine in patients with cervical spondylosis. Materials and Methods: The preliminary study included 29 patients with cervical spondylosis, of mean age (Mean(SD)) 59.9(11.6) years (20 women 62.0(10.0) and 9 men 55.3(14.2)). The duration of the current pain episode is 5(2-16) weeks, and the average duration (Me(Range)) of the disease is 8(1-19) years. Patients conducted 10 sessions with TENS and therapeutic exercises. The results were scored before therapy and after rehabilitation, by assessing pain (VAS) and range of motion in the cervical spine by goniometry. Results: We observed a decrease in pain (Mean(SD)) from 4.86(0.95) to 2.14(0.95);p<0.05 and an increase in the range of motion in the cervical spine after the rehabilitation program. In the sagittal plane: Extension from 41.03(12.20) to 56.21(10.32);p<0.05, Flexion from 39.83(9.68), 53.10(8.70);p<0.05. Rotation in left from 41.55(13.30) to 53.28(12.91);p<0.05, Rotation in right from 38.97(14.04) to 50.0(14.08);p<0.05. Lateroflexion on the left from 27.41(7.28) to 35.0(6.94);p<0.05, Lateroflexion on the right from 23.62(6.67) to 33.45(6.96);p<0.05. Conclusion: The results of the conducted preliminary study showed a reduction in pain and an increase in the range of motion in the cervical spine. Therapy with TENS and therapeutic exercise could be an effective non-pharmacological therapeutic option in the treatment of patients with cervical spondylosis. For better objectification of the obtained results it is necessary to continue the research.